Texture dough machine / Muhammad Afiq Amsyar Mohamad Yusri - Mohamad Yusri, Muhammad Afiq Amsyar (2023)
A dough texture machine is a machine that kneading and spreading a dough mechanically. There are various variants related to this dough machine. However, the use and methods of using it are different in terms of savings and efficiency. The best impact at the end product will conclude the best aspect of item. But some people need energy and skill to knead the dough traditionally. By using this machine, it can reduce time and even labor in making texture dough. They only need to use the machine in the right way and it will produce the final product as planned. In addition, some additional features are added to the machine for the convenience of the user so that it does not take a long time to spread the dough. My objective in doing this project is to analyze and modify this device and the existing one for daily use based on the target type of people targeted. In conclusion, I hope my project can help people solve the problem.